Can we raise the threshold for negative fetal fibronectin result?. (18th April 2012) - Karunakaran, B; Berry, J; Parasuraman, R
Abstract : Quantitative fetal fibronectin (fFN) measurement in asymptomatic women has been previously shown to delineate the risk of preterm labour. Objective: To determine if a quantitative fFN result correlated with the risk of subsequent preterm birth in women presenting with threatened preterm labour and if the level reported as negative (currently <50ng/ml) could be increased. Method: Retrospective audit of all fFN results in women who attended our day unit since the introduction of quantitative fFN testing with review of delivery details. Results: Of 79 women tested for fFN since the introduction of quantitative testing, 17 were excluded (incomplete data available, iatrogenic delivery, invalid result). Of 62 women remaining, the gestational age at test ranged from 24+4 to 34+1 (mean 30+6, median 31). 51 patients had a negative fFN and 11 had a positive result. The delivery rate <34 weeks gestation was 8% overall (5/62) and 36% in those with positive fFN (4/11). Of the preterm deliveries, 1 had a negative fFN (<50ng/ml) giving a false negative result of 1.96%. Using a threshold of 200ng/mL would not have altered this. 4 (36%) patients with a positive fFN went on to deliver at <34 weeks gestation. If the negative threshold was increased to 200ng/mL this improved the true positive rate to 66.7% without increasing the number of false negatives. Conclusion: It might be possible to safely raise the threshold for diagnosing a positive fFN result. These are very small numbers and this audit is currently ongoing to improve the significance of the results.